2021
DOI: 10.3390/medicina57020186
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Glomerulonephritis

Abstract: Vitamin D presents a plethora of different functions that go beyond its role in skeletal homeostasis. It is an efficient endocrine regulator of the Renin–Angiotensin–Aldosterone System (RAAS) and erythropoiesis, exerts immunomodulatory effects, reduces the cardiovascular events and all-cause mortality. In Chronic Kidney Disease (CKD) patients, Vitamin D function is impaired; the renal hydrolyzation of its inactive form by the action of 1α-hydroxylase declines at the same pace of reduced nephron mass. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 142 publications
0
27
0
1
Order By: Relevance
“…Thus, vitamin D acts as a real steroid hormone and its level is influenced by estrogen status [ 133 ]. It exerts a modulating action at both tubular [ 134 ] and glomerular level [ 135 ], with peculiar protective action in DKD [ 136 ]. Moreover, pre- and post-menopausal DM women with an adequate vitamin D status seem to have a better glycemic control [ 137 ].…”
Section: Impact Of Female Sex Hormones On Dkdmentioning
confidence: 99%
“…Thus, vitamin D acts as a real steroid hormone and its level is influenced by estrogen status [ 133 ]. It exerts a modulating action at both tubular [ 134 ] and glomerular level [ 135 ], with peculiar protective action in DKD [ 136 ]. Moreover, pre- and post-menopausal DM women with an adequate vitamin D status seem to have a better glycemic control [ 137 ].…”
Section: Impact Of Female Sex Hormones On Dkdmentioning
confidence: 99%
“…Vitamin D acts as a real steroid hormone and its level is influenced by estrogen status 17 with protective action in DKD 18 . Vitamin D supplementation has also been demonstrated to significantly reduce proteinuria and slow kidney disease progression 19 …”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the pleiotropic effects that vitamin D exerts to prevent different conditions leading to renal impairment [ 58 , 59 , 60 ] to modulate renin-angiotensin-aldosterone system and to reduce CV risk [ 61 ], a connection with this hormone has not been fully validated in CRS patients. Mann et al [ 62 ] demonstrated that deficient serum levels of vitamin D are linked to a suppression of resting cardiac autonomic activity, while low 1,25-dihydroxy vitamin D levels correlated with unfavorable cardiac autonomic activity during an acute angiotensin II stressor challenge.…”
Section: Biomarkers Connecting the Heart And Kidneymentioning
confidence: 99%